Soil Bacterial Diversity and Productivity of Coffee - Shade Tree Agro-ecosystems - Evizal, Rusdi; Tohari, .; Prijambada, Irfan Dwidja; Widada, Jaka; Widianto, Donny (JOURNAL OF TROPICAL SOILS, 2012)
Coffee productions should have environmental value such as providing high soil microbial diversity while producing high yield. To examine that purposes, two experimental plots were constucted at benchmark site of Conservation and Sustainable Management of Below-Ground Biodiversity (CSM-BGBD), in Sumberjaya Subdistrict, West Lampung, Indonesia, during 2007-2010. Types of coffee agro-ecosystem to be examined were Coffea canephora with shade trees of Gliricidia sepium, Erythrina sububrams, Michelia champaca, and no shade. Two plots were constructed at 5-years-coffee and 15-years-coffee. Diversity of soil bacteria was determined based on DNA finger printing of total soil bacteria using Ribosomal Intergenic Spacer Analysis (RISA) method. The results showed that: (1) For mature coffee (15 years old), shade-grown coffee agro-ecosystems had higher soil bacterial diversity than those of no shade coffee agro-ecosystem, (2) Shaded coffee agro-ecosystems were able to conserve soil bacterial diversity better than no-shade coffee agro-ecosystem. Soil organic C and total litter biomass had positive effect on soil bacterial diversity, (3) Types of agro-ecosystem significantly affect the bean yield of 15 years coffee. Coffee agro-ecosystems shaded by legume trees had higher yield than those of non-legume shade and no shade coffee agro-ecosystem, (4) Shannon-Weaver indices of soil bacterial diversity together with weed biomass and N content of coffee leaf had positive effect on coffee bean yield.